Eosinophilic Granulomatosis with Polyangiitis Manifesting as Recurrent Nasal Polyps and Hemorrhagic Necrotic Bullae: A Rare Disease Successfully Treated with Azathioprine - Abdulaziz Alotaibi; Stefan W. Schneider (Karger Publishers, 2019)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare multisystemic vasculitis which was previously called Churg-Strauss syndrome or allergic granulomatosis. It has an unknown pathogenesis, possibly autoimmune in nature. As it has a low incidence, there is only scant published literature. This case report is valuable to dermatologists, since skin involvement is one of the most common features of the vasculitic phase. This report represents one of the possible presentations of EGPA according to the antineutrophil cytoplasmic antibody status - which in our case was negative, with a low prognostic Five-Factor Score - that was successfully treated with oral steroids and azathioprine as a steroid-sparing agent. Our objective was to add a case report to the scarce existing literature in order to learn more about therapeutic options for EGPA. This case report demonstrates that oral steroids, as induction treatment, and azathioprine, as maintenance treatment, are effective in elderly patients with EGPA without involvement of any other organs. Nevertheless, additional studies are necessary to achieve appropriate management.